Plasma xenin concentrations in children - Beata Mrózek; Przemysław J. Tomasik; Andrzej Wędrychowicz; Małgorzata Wójcik; Szymon Skoczeń; Krzysztof Fyderek; Jerzy Starzyk; Krystyna Sztefko (Termedia Publishing House, 2012)
Introduction: Xenin is a newly discovered peptide in humans. The concentration of xenin in human plasma increases after meals and therefore this peptide is considered as a marker of satiety. The mechanism of xenin action in humans has not been thoroughly examined. MEDLINE database contains only few reports about the role of xenin in adults and none of them were performed in children. Aim of the study: The aim of the study was to evaluate the concentration of xenin in children with energy balance disorders. Material and methods: Plasma xenin concentration was measured in children with inflammatory bowel syndrome (IBD) (n=53; age 14±3 years) before, during and after treatment, obese children (n=26; age 14±2.8 years) during the OGGT test and in healthy children (n=10; age 15.7±2.2 years). Xenin was determined in the plasma using the radioimmunological method. Results: The mean plasma xenin concentration in the healthy children was 371±36 pg/ml. In the children with an acute phase of IBD the mean concentration of xenin was 367±96 pg/ml and an increase during the treatment to the mean value 399±55 pg/ml was noted. The highest mean value of xenin concentration (412±55 pg/ml) was found during early remission. In obese children, the mean concentration of xenin (198±69 pg/ml) was significantly lower as compared to children with IBD and to control (p<0.001 in both cases). The glucose load did not have any effect on xenin concentration in obese children. Conclusions: Xenin takes part in the regulation of energy balance in children.